ONLINE SELLING REGISTERS IN FACEBOOK GROUP SELLING AND BUYING ANYTHING AND THE IMPLEMENTATION OF THE LEARNING OF INDONESIAN LANGUAGE IN SMA - Ediwarman Ediwarman; Syafrizal Syafrizal; John Pahamzah (Kajian Linguistik dan Sastra, 2020)
The purpose of this study is to describe the form of abreviation and function of the register language in the Facebook group "Buy and Sell Anything Cilegon Serang Banten". The method used in this research is qualitative method. As for the data collected through library study techniques, refer to the basic tapping techniques and advanced techniques of free and accountable, note taking, and documentation techniques. The data obtained are classified based on the form of abreviation and register language functions. Based on the results of the study found 4 forms of abreviation consisting of 1) abbreviations, 2) acronyms, 3) fragments, and 4) letter symbols. In addition, 5 language functions were found consisting of 1) instrumental functions, 2) representational functions, 3) interactional functions, 4) personal functions, and 5) heuristic functions. The results of this study can be implemented in Indonesian language learning in high school, especially in negotiating text learning.Keywords: Facebook, register, form of abreviation, language functions